Food Derived Biostimulants Technology Revealed and Retrieved by Natural Language Processing - Kobayashi, Yoshiyuki; Ota, Kakeru; Iwano, Maya; Kageyama, Itsuki; Kodama, Kota; Tsuda, Kazuhiko (EAI Endorsed Transactions on Scalable Information Systems, 2025)
Food-derived biostimulants support sustainable agriculture; however, the scale and heterogeneity of the field hinder their synthesis. We profiled 2005–2025 innovation by mining 2,586 PATENTSCOPE filings and Web of Science articles; texts were analyzed with KH Coder and topic models, with large language models assisting in interpretation. Patent activity surged after 2018, emphasizing plant growth promotion, yield stability, and abiotic stress tolerance (amino acids, seaweed extracts, polyphenols, humic substances, and microbial consortia). In parallel, academic papers have shifted from descriptive trials to mechanism-level work on drought/salinity responses, gene expression, and metabolomics. Together, these signals outline a translation path in which deployable biological inputs converge with mechanistic evidence. Our NLP pipeline distilled heterogeneous texts into actionable indicators, yielding a reproducible map from patent/literature trends to testable hypotheses for formulation, dose, and seed stage delivery.
Keywords: Biostimulants; Sustainable agriculture; Health information science; Text mining; Patent analysis